2018
DOI: 10.1177/1524838018806507
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Interpersonal Violence Among Latinas: A Systematic Review

Abstract: Violence against women continues to be a great concern in today’s society. In the United States, women experience high rates of interpersonal violence throughout their lifetime. Among Latinas, interpersonal violence is also highly prevalent however the wide variation of interpersonal prevalence rates among Latinas is problematic. The aims of this systematic review of the literature were to (1) document the prevalence rates of violence among Latinas, (2) determine the types of violence that Latinas are most imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 63 publications
1
46
0
1
Order By: Relevance
“…Although recent data may be lacking due to the interruption of routine work practices and healthcare visits due to the COVID-19 pandemic, some studies have suggested that the incidence and prevalence of DV and IPV may be increasing in some areas, including Nevada [ 49 , 50 ]. These data support the official position statement of the American College of Preventive Medicine that IPV and DV are important sociomedical problems that deserve professional, academic, and curricular attention to help provide capable, competent, and engaged healthcare providers with sufficient knowledge and awareness, not only of this issue, but of the resources and referrals that may help provide care and support for patients experiencing DV or IPV [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although recent data may be lacking due to the interruption of routine work practices and healthcare visits due to the COVID-19 pandemic, some studies have suggested that the incidence and prevalence of DV and IPV may be increasing in some areas, including Nevada [ 49 , 50 ]. These data support the official position statement of the American College of Preventive Medicine that IPV and DV are important sociomedical problems that deserve professional, academic, and curricular attention to help provide capable, competent, and engaged healthcare providers with sufficient knowledge and awareness, not only of this issue, but of the resources and referrals that may help provide care and support for patients experiencing DV or IPV [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although certain ethnoracial minority groups have high levels of trauma exposure and various trauma types, including exposure to war‐related trauma (Roberts, Gilman, Breslau, Breslau & Koenen, 2011), natural disasters (Bryant, 2006; Udomratn, 2008), traumatic experiences before immigrating to the United States or during the immigration process (Benuto & Bennett, 2019; Cleary, Snead, Dietz‐Chavez, Rivera, & Edberg, 2018), violence (Gonzalez, Benuto, & Casas, 2018; Roberts et al., 2011) and racial discrimination (Pérez, Fortuna, & Alegría, 2008), to name a few, there is a discrepancy between a diagnosable mental health condition and behavioral health service use (Le Meyer, Zane, Cho & Takeuchi, 2009). Mendoza and colleagues (2012) posited that underrepresentation may be a cultural barrier that restricts the patient from fully expressing symptoms in a way that the clinician can understand, contributing to possible underdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research has estimated considerable variability in that anywhere between 15% to 80% percent of Latinas will experience some form of psychological controlling behaviors, physical violence, and/or sexual violence at the hands of an intimate partner in their lifetime (Cavanaugh et al, 2014; Sabina et al, 2015). Most recently, Gonzalez et al (2018) systematically reviewed 41 studies published over the span of ten years to assess the prevalence of IPV among Latinas and concluded that the true estimate still remains unknown. Similarly, data from the Centers for Disease Control and Prevention (CDC) has relied solely on ethnicity to capture an IPV prevalence of 34.4% for “Hispanic” women (Smith et al, 2017).…”
Section: System Responses To Latina Ipv Victims Through a Latcrit Frameworkmentioning
confidence: 99%